Dr. Menstrual cup as an alternative to sanitary pads for preventing recurrence of tinea cruris : replacing pads with menstrual cup can prevent recurrence of tinea - Jindal, Anuradha; Mysore , Venkataram; Noronha , Malcom; Mysore , Jayashree Venkataram (Journal of Pakistan Association of Dermatologists, 2023)
The current prevalence of superficial mycotic infections worldwide has been estimated to be 20-25% as per World health organisation. Millions of women across globe rely on sanitary pads or panty liners for feminine hygiene protection. Most of the sanitary pads have similar design and are made of three layers - with top layer consisting of fluid permeable surface, an absorbent core and impermeable back cover with adhesive layered on its back. It was observed that the mean temperature of the labia majora was 1.5Â°C higher than the females without the panty liners. The penetration of fungal elements of trichophyton mentagrophytes is much faster with increased humidity and temperature. The alternative use of menstrual cup instead of. Sanitary pads acan prevent the re-emergence of tinea cruris periodically.